Morphology of the temporal skull region in tetrapods: research history, functional explanations, and a new comprehensive classification scheme. (31st May 2021) - Abel, Pascal; Werneburg, Ingmar
ABSTRACT: The morphology of the temporal region in the tetrapod skull traditionally has been a widely discussed feature of vertebrate anatomy. The evolution of different temporal openings in Amniota (mammals, birds, and reptiles), Lissamphibia (frogs, salamanders, and caecilians), and several extinct tetrapod groups has sparked debates on the phylogenetic, developmental, and functional background of this region in the tetrapod skull. This led most famously to the erection of different amniote taxa based on the number and position of temporal fenestrae in their skulls. However, most of these taxa are no longer recognised to represent natural groupings and the morphology of the temporal region is not necessarily an adequate trait for use in the reconstruction of amniote phylogenies. Yet, new fossil finds, most notably of parareptiles and stem‐turtles, as well as modern embryological and biomechanical studies continue to provide new insights into the morphological diversity of the temporal region. Here, we introduce a novel comprehensive classification scheme for the various temporal morphotypes in all Tetrapoda that is independent of phylogeny and previous terminology and may facilitate morphological comparisons in future studies. We then review the history of research on the temporal region in the tetrapod skull. We document how, from the early 19th century with the first recognition of differences in the temporal region to the first proposals of phylogenetic relationships and their assessment over the centuries, the phylogenetic perspective on the temporal region has developed, and we highlight the controversies that still remain. We also compare the different functional and developmental drivers proposed for the observed morphological diversity and how the effects of internal and external factors on the structure of the tetrapod skull have been interpreted.